The Relationship between Safety Culture and Risk Management on Patient Safety Incidents in the Inpatient Room at Stella Maris Hospital, Makassar - Lilian Ishak; Yulia Yasmi (Formosa Journal of Science and Technology, 2024)
Building a culture of safety and risk management is an important element to improve patient safety and quality of service. The aim of this research is to identify the relationship between Safety Culture and Risk Management on Patient Safety Incidents in the Inpatient Room at Stella Maris Hospital, Makassar. The research method uses a descriptive approach, with a cross sectional method. The research sample was 57 nurses in the Inpatient Room at Stella Maris Hospital, Makssar, using a simple random sampling technique. From the results of the Spearman correlation test, it was found that the correlation coefficient (r) = 0.575, which means that the level of strength of the relationship (correlation) between risk management and patient safety incidents is 0.575 or very strong. The correlation coefficient number is positive which indicates a unidirectional relationship, the resulting Sig value. (2-tailed) 0.000 where this result is <0.05, there is a significant relationship between risk management and patient safety incidents. The conclusion and implementation of the research results is that a good safety culture and risk management will reduce patient safety incidents and improve the quality of service and patient safety